2022
DOI: 10.1080/17512433.2022.2108401
|View full text |Cite
|
Sign up to set email alerts
|

The role of CYP2C19 genotyping to guide antiplatelet therapy following ischemic stroke or transient ischemic attack

Abstract: Introduction Clopidogrel is an antiplatelet agent recommended for secondary prevention of ischemic stroke (IS) and transient ischemic attack (TIA). Conversion of clopidogrel to its active metabolite by hepatic cytochrome P450-2C19 (CYP2C19) is essential for the inhibition of the P2Y12 receptor and subsequent platelet aggregation to prevent thrombotic events. CYP2C19 is highly polymorphic, with over 30 loss of function (LoF) alleles. This review considers whether there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 99 publications
0
9
0
Order By: Relevance
“…Additionally, the frequency of rapid and poor metabolizer groups in India, which exhibit a pattern comparable to the results of the CYP2C19 genotyping in European and East Asian nations, suggests that the geographical element may also be connected to the pattern. 10 , 11 A study on Tamilians suggests the distribution of CYP2C19∗1/∗1 being lower than Caucasians, Africans, and North Indians, but a notably higher frequency of CYP2C19∗1/∗2 compared to other populations; whereas the CYP2C19∗1/∗3 allele was reported in 2.7% Tamilians, the same was not reported in North Indian and Caucasians. 12 Thus, the allele frequencies in South Indian populations were found to be distinct from Caucasians and Chinese, 13 this confirms the variable racial distribution of CYP2C19 alleles among different ethnic groups, with each ethnic group having a mate selection bias that may cater to inbreeding (either strict caste endogamy or consanguinity), rendering deviation from HWE.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the frequency of rapid and poor metabolizer groups in India, which exhibit a pattern comparable to the results of the CYP2C19 genotyping in European and East Asian nations, suggests that the geographical element may also be connected to the pattern. 10 , 11 A study on Tamilians suggests the distribution of CYP2C19∗1/∗1 being lower than Caucasians, Africans, and North Indians, but a notably higher frequency of CYP2C19∗1/∗2 compared to other populations; whereas the CYP2C19∗1/∗3 allele was reported in 2.7% Tamilians, the same was not reported in North Indian and Caucasians. 12 Thus, the allele frequencies in South Indian populations were found to be distinct from Caucasians and Chinese, 13 this confirms the variable racial distribution of CYP2C19 alleles among different ethnic groups, with each ethnic group having a mate selection bias that may cater to inbreeding (either strict caste endogamy or consanguinity), rendering deviation from HWE.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the population prevalence of pharmacogenetics CYP2C19*2 polymorphism14, this result suggests that patients with a resistance phenotype have a higher risk of stroke on clopidogrel treatment and require special medical care. Indeed, 26% of patients of European ancestry are classified as CYP2C19 IM [13,14]. Consequently, they have a higher risk of stroke relapse due to antiplatelet resistance [14].…”
Section: Discussionmentioning
confidence: 99%
“…Recent scientific literature proposed guidelines for the interpretation of pharmacogenetics and its consequences on prescriptions [7,[18][19][20]. Level of evidence is debated according to scientific literature, in particular, in stroke for CYP2C19 genotyping [13]. In patients with pharmacogenetics resistance to clopidogrel, P2Y12 inhibitors not metabolised by CYP2C19 such as ticagrelor could be a therapeutic alternative, considering the benefit-risk balance (risk of thrombosis versus bleeding) [13].…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have reported reduced active metabolite formation and platelet inhibition in poor and/or intermediate metabolizers vs the normal or rapid ones, the clinical impact of each CYP2C19 allele status and their multiple combinations is not fully established. Some retrospective studies and posthoc analyses of randomized clinical trials that pooled patients with intermediate- and poor-metabolizer genotypes showed a higher rate of serious vascular events or stent thrombosis as compared with extensive metabolizers [ 40 , 71 , 72 ]. Other studies have shown a lack of clopidogrel efficacy in poor but not intermediate metabolizers, as compared to extensive metabolizers [ 40 ].…”
Section: P2y 12 Blockers and Precision Dosingmentioning
confidence: 99%